Renewable bleaching alternatives (RBA) for palm oil refining from waste materials - Ismail, Muhammad Imran; Hamidon, Muhammad Hazim; Mohd Sofi, Mohd Zulhilmie; Azmi, Nur Shahirah (2016)
Bleaching process is one of the crucial processes in palm oil refining. An adsorbent known as bleaching clay is widely used in the palm oil refining industry to adsorb the unwanted color pigments and a wide range of other impurities. A study was carried out to seek for adsorbents alternatives that possess similar characteristics to bleaching clay from renewable sources. Three different adsorbents which are peanut hulls from peanuts, press mud from sugar refinery waste and rice husks from the paddy process plant were chosen. These renewable bleaching alternatives from waste materials were chosen because of their characteristics, which are able to adsorb unwanted substances in crude palm oil. The analysis of free fatty acids (FFA), Peroxide value (PV), carotene value and color was carried out to analyze the characteristics. The characteristics of each alternative were examined and tested to analyze their bleaching efficiency. The conducted analysis has proven that press mud was able to adsorb the greatest value of FFA in crude palm oil, as well as reducing the color of crude palm oil to the desired color in bleached palm oil with bleaching clay. Crude palm oil bleached with press mud has the lowest value of FFA and color.